Penerapan Model TGT Berbantuan Media Puzzle Terhadap Keterampilan Membaca Aksara Jawa Kelas IV Sekolah Dasar - Puspitasari, Nasyaauliya; Much Arsyad Fardani; F. Shoufika Hilyana (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2025)
Learning Javanese is considered difficult by elementary school students, especially in Javanese script material. This can be seen based on the value of Javanese script reading skills that have not met the KKTP, the cause of low student scores is due to the different abilities of each student and students assume that learning Javanese is very difficult to understand and boring. In addition, the lack of variation in learning models applied by teachers seems monotonous, and is not accompanied by learning media so that students are passive and not interested in participating in learning. This study aims to determine the increase in the TGT learning model assisted by puzzle media on the Javanese script reading skills of grade IV elementary school students. The implementation of the study was located at SDN 4 Getassrabi with a quantitative research method Pre-Experimental Design. Data acquisition comes from the pre-test with the aim of determining the initial abilities of students before being given treatment. And the post-test was carried out after being given treatment. The results of this study showed a percentage value of N-Gain of 59% with fairly effective improvement criteria. Therefore, the use of the TGT learning model assisted by puzzle media on the Javanese script reading skills of grade IV students has experienced an effective increase for us